Real Estate as a Hedge Against Inflation - Marsella, F N U (Archives of Business Research, 2025)
Real estate has long been considered a strong inflation hedge. Amid concerns about increasing inflation and interest rates, this study investigates which real estate asset classes exhibit superior hedging characteristics against both ex-pected and unexpected inflation. The primary contribution of this study is a recommendation for real estate portfolio allocation that optimizes the use of real estate as a hedge against inflation. Using NARET & NCREIF indices as proxy, industrial was found as the best overall inflation hedge followed by multifamily, office, hotel, and retail. The im-portance of hedging characteristics, however, was shown after decomposing CPI into expected and unexpected components. In this case, hotel perform best in period of expected inflation while industrial and multifamily, on the other hand, demonstrate better hedging ability for unexpected inflation. Comparing the public and private real estate markets, public real estate act as a better hedge in an expected inflationary environment, with exception to the hotel class. The private real estate, however, outperforms on a relative basis in periods of unexpected inflation.